Acute Hematogenous Osteomyelitis in a Five-Month-Old Male with Rickets - Lucia J. Santiago; Minnie John; Maher Abulfaraj; Christabelle Co; Aseel Al-Jadiri (Case Reports in Pediatrics)
Osteomyelitis is defined as an infection of the bone, bone marrow, and the surrounding soft tissues. Most cases of acute hematogenous osteomyelitis in children are caused by Gram-positive bacteria, principally Staphylococcus aureus. We present a case where a 5-month-old male had an acute onset of decreased movement of his left leg and increased irritability and was subsequently diagnosed with rickets and hematogenous osteomyelitis with bacteremia. The case explores a possible association between hematogenous osteomyelitis and rickets.